Water productivity of irrigated wheat and maize in the Karkheh River Basin of Iran - Qureshi, Asad Sarwar; Oweis, Theib Y.; Karimi, Poolad; Porehemmat, J. (Wiley, 2009)
Karkheh River Basin (KRB) is the third largest and most productive river basin of Iran. The major agricultural issue of KRB is low water use efficiencies. Farmers' irrigation practices are aimed at maximizing crop production through excessive use of irrigation water resulting in huge water losses. As the opportunities for water resources development in KRB are very limited, improving the productivity of existing water resources is the most attractive option to produce more food for the increasing population. This paper analyzes water productivity of irrigated wheat and maize in the KRB. The results reveal that farmers having access to groundwater tend to apply higher irrigation amounts. Relatively higher crop yields in irrigated areas are also linked to higher nitrogen use, which can create serious problems of groundwater contamination in future. Due to excessive use of groundwater and fertilizer, production costs have increased resulting in low gross margins (farm incomes). The study suggests that increase in charges for surface water use removal of subsidies on electricity will discourage excessive use of water for agriculture. Furthermore, farmers should be trained to optimize irrigation water and fertilizer application in order to save scarce water resources and reduce production costs and increase farm returns. These steps are of great importance for ensuring sustainability of irrigated agriculture and to alleviate poverty in rural areas of KRB.